Verba KAMU dan KAJIRU Sebagai Sinonim Dalam Kalimat Bahasa Jepang (Kajian Sintaksis Semantik) - Yanti Hidayati; Nunik Nur Rahmi Fauzah; Riza Mawarni (KIRYOKU, 2023)
In Japanese, synonym is called ruigigo. Kamu and kajiru are synonymous verbs that mean 'to bite'. This discussion analyzes the meaning of kamu and kajiru as seen from the subject structure (animate or inanimate) and the object in the sentence. This study employs a descriptive analysis that uses the discussion object in Japanese sentences jitsurei containing kamu and kajiru. Data collection was observing and note-taking. The website nlb.ninjal.ac.jp is the data source. Data analysis uses the billing method.This study found that there are similarities and differences in meaning seen from the syntactic and semantic research contained in kamu and kajiru in a sentence that has the meaning of 'biting' in Indonesian based on the sentence context. Furthermore, kamu and kajiru can be paired with both animate and inanimate subjects and food and non-food objects. Their difference in meaning is found in subject and the characteristics of the object. The meaning of kamu verb is to bite, chew, and crush an object with teeth, while kajiru verb emphasizes the meaning of biting from the edge of the object and can be paired with more specific inanimate subjects of a rodent.